Analisis Kebutuhan Pengembangan Media Pembelajaran Powerpoint Interaktif Materi Volume Balok dan Kubus Berbasis Kontekstual untuk Siswa Kelas V SDN Kraton - Putri, Shintya Eka Rosalia; Permana, Erwin Putera; Damariswara, Rian (Universitas Nusantara PGRI Kediri, 2023)
Needs analysis is the initial activity for achieving the learning objectives, including one in mathematics learning. Need analysis provides in-depth information as a benchmark for developing learning media. The aim of this research is to analyze the needs of contextual-based interactive PowerPoint learning media development for students of the V class of SDN Kraton. This developmental research uses descriptive analysis modes, lifting instruments as data collection. Based on the results of this research, it can be concluded that the analysis results of the need for media development interactive learning media PowerPoint contextual based obtained a positive response. This research can be developed on the development of interactive PowerPoint learning media volume material bars and cubes contextual-based for V-Class students of SDN Kraton.